Strategi Koperasi Syariah TKI Artha Mulya dalam Meningkatkan Perekonomian Purna TKI - Abdullah Zawawi; Wulandari, Erni (Institut Pesantren Sunan Drajat Lamongan, Indonesia, 2024)
The Artha Mulya TKI Cooperative is a Sharia Cooperative founded by TKI and retired TKI. The Artha Mulya TKI Sharia Cooperative has a market segment that includes the middle to lower levels of society. This research aims to answer, describe and analyze the problem formulation, namely 1. What is the Strategy of the Artha Mulya TKI Cooperative in Improving the Economy of Retired TKI through Creative Economy activities. 2. What are the obstacles and solutions for the TKI Artha Mulya Sharia Cooperative in improving the economy of retired TKI through creative economic activities. The research method used in this research is descriptive qualitative, namely a research method based on scientific objects. And the research instruments used to collect data are observation, interviews and documentation. The Artha Mulya TKI Sharia Cooperative has become popular and close to the community. The results of this research concluded that: (1) The Artha Mulya TKI Sharia Cooperative has several strategies to help improve the economy of its members and the wider community, namely borrowing business capital, creating business groups, holding business training, supplying raw goods, marketing production results, helping with paperwork. permission, while the strategy for the TKI Artha Mulya Sharia Cooperative in improving the economy of retired TKI through creative economic activities is to create a creative economic business in the form of a snack making business with the name